FACTORS THAT INFLUENCE WOMEN STAFF OF UNIVERSITY UTARA MALAYSIA TO PRACTICE RASULULLAH’S S.A.W. METHODOLOGY IN CHILDREN EDUCATION - Syed Sultan Bee (Journal of Islamic, Social, Economics and Development, 2018)
Parents are fully responsible to educate their children using the right and proper way. This is to save them from falling into social problems and moral decline which are increasing among teenagers lately. The increasing of social problems indirectly shows that there are imperfections and mistakes made by parents today in educating their children. Hence, parents need to be given the awareness on the importance of educating children by practicing the correct methodology, namely Rasulullah's s.a.w. methodology as the solution to this problem. Consequently, a quantitative study was conducted to investigate the factors that influence women staff of University Utara Malaysia (UUM) to practice Rasulullah's s.a.w. methodology in children education. This study involves a total of 306 respondents consisting the administrative and academic staff. Questionnaires were used to collect data while Statistical Packages for Social Sciences (SPSS) version 22.0 was used to analyze the collected data. The findings of the study show that majority among the women staff of UUM agreed that family, environment, education, mass media and self-awareness factors have influenced them to educate their children by practicing Rasulullah’s s.a.w. education methodology. The outcome of this study is expected to give parents awareness to practice Rasulullah’s s.a.w. methodology in educating children in order to decrease social problems among younger generation in this country, besides producing more Muslim individuals with good moral and personality.